Polsko-rosyjskie i rosyjsko-polskie słowniki przekładowe. Bibliografia za lata 1990-2005 w układzie chronologicznym - Wojan, Katarzyna (Przegląd Rusycystyczny, 2006)
BIBLIOGRAPHY OF POLISH-RUSSIAN AND RUSSIAN-POLISHDICTIONARY WORKSOF THE PERIOD 1990-2005 Summary For the first time in Polish lexicography author describes Polish-Russian and Russian-Polishdictionary works of the period 1990Œ2005. The dictionaries are arranged according to the chrono-logical and alphabetical principles. The index is the first experience of systematizing lexicographi-cal works and is the part of complete bibliography Russian Language in the Polish Lexicography.